Studi Eksposisi Kejadian 12:1-9 : Perjanjian Allah dengan Abraham dan Implikasinya bagi Iman Kristen Masa Kini - Mintaria. M. Is Thomes; Damaris Advin Jeliner Nubatonis; Malik Bambangan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The covenant between God and Abraham serves as proof that God is a faithful God who never abandons His people, whether in times of joy or sorrow. This covenant is also one of the fundamental covenants in the Old Testament, with significant theological and historical implications. This article, we’re discusses and analyzes God’s covenant with Abraham and its implications for Christian faith today, based on Genesis 12:1-9. Through this covenant, God promises three main things to Abraham: numerous descendants, the promised land, and blessings for all nations. Futhermore, this covenant serves as the foundation of Israel’s identity and finds its fulfillment in Jesus Christ, as foretold in Genesis 3:15, namely the offspring that will be born a woman. This study serves as evidence and a model for Christians regarding Abraham’s obedience and steadfast faith, emphasizing that salvation in Jesus Christ is one of God’s fulfilled promises to Abraham. Thus, understanding this covenant strengthens the conviction that God remains faithful to His promises and that faith in Him is the foundation of true spiritual life for believers.